THE INFLUENCE OF PROMOTIONAL ADVERTISING COSTS ON SALES IN FMCG COMPANIES LISTED ON THE BEI - Saffela, Nurika Indah; Pangestika, Nasilem; Khairudin, Agus (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2024)
This article examines the effect of promotional advertising costs on sales in Fast-Moving Consumer Goods (FMCG) companies listed on the Indonesia Stock Exchange for the period 2021 to 2023. In this study using quantitative methods with sampling using secondary data on the financial statements of Fast-Moving Consumer Goods (FMCG) companies listed on the Indonesia Stock Exchange for the period 2021 to 2023. The sampling technique was carried out using non-probability sampling with purposive sampling technique. So that the sample obtained was 18 Fast-Moving Consumer Goods (FMCG) companies listed on the Indonesia Stock Exchange for the period 2021 to 2023 with a total observation data of 54 for 3 years of observation. The purpose of this study is to provide empirical evidence regarding the effect of promotional costs on sales. The results showed that promotional advertising costs have a positive and significant effect on sales of FMCG companies on the Indonesia Stock Exchange, with a contribution of 56.5% to the sales variable. To increase sales effectiveness, FMCG companies need to identify and manage other variables that also affect sales. Further research can be conducted to include additional variables and provide a more comprehensive picture of the factors that influence sales in the FMCG sector.